THE EFFECT OF FINANCIAL PERFORMANCE ON COMPANY VALUE IN TELECOMMUNICATION COMPANIES LISTED ON THE INDONESIA STOCK EXCHANGE - Indra Nugraha; Mas Ning Zahroh (Asosiasi Dosen Muda Indonesia, 2023)
The sample used in this study were 4 telecomunication sector companies listed on Indonesian Stock Exchange period 2013-2017 with purposive sampling. The indicators used are ROA for Profitability, DER for Solvability, CR for Liquidity and PBV for Firm Value. Data collection techniques use financial statements originating from the Indonesia Stock Exchange. The analysis technique used is Multiple Linear Regression.The result of this study indicate profitability has a positive and significant effect on firm value, solvency does not have a significant effect on firm value, liquidity has a positive and significant effect on firm value. Simultaneously profitability, solvability and liquidity affect the firm value.